On Certain Inequalities for Neuman-Sándor Mean - Wei-Mao Qian; Yu-Ming Chu (Abstract and Applied Analysis)
We present several new sharp bounds for Neuman-Sándor mean in terms of arithmetic, centroidal, quadratic, harmonic root square, and contraharmonic means.